Mechanosynthesis of N-Methyl Imines Using Recyclable Imidazole-Based Acid-Scavenger: In Situ Formed Ionic Liquid as Catalyst and Dehydrating Agent - Khaligh, Nader Ghaffari; Ong, Chiu Ling; Mihankhah, Taraneh; Johan, Mohd Rafie; Juan, Joon Ching (CSIRO Publishing, 2019)
1,1′-(1,4-Butanediyl)bis(imidazole) was prepared by a modified method and its application as an efficient promoter was demonstrated for the mechanosynthesis of N-methyl imines using ball milling as a non-conventional process under solvent-free conditions. In this new protocol design, the bis-imidazole acted as a recyclable acid-scavenging agent. This efficient approach to the N-methyl imines displays a combination of the synthetic virtues of a non-conventional condensation reaction with ecological benefits and convenience of a facile mechanosynthetic process. The current method has advantages such as reduced waste by avoiding solvent, exclusion of hazardous materials during the reaction, elimination of handling an anhydrous gas in an evacuated container or a solution of methylamine in ethanol, good yields for relatively unreactive benzaldehydes containing electron-donating substituents, short reaction times, and metal- and acid-free conditions. Furthermore, the promoter was easily regenerated and reused several times with no significant loss of activity. © 2019 CSIRO.